SPECIFIC CHARACTERISTICS OF TEXT CATEGORY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
In this article is discussed about specific characteristics of text category and also given information scholars why are searching on this field. These days, linguists' responses to queries concerning a text's status, its meaning within the language system, and the best place to start a linguistic analysis of a text are often ambiguous. For instance, we occasionally come across differing viewpoints regarding the matter of establishing a text's status. Divergent perspectives exist concerning the nature of the text's signs, whether it is better to refer to the text as a speech process or to understand it as the outcome of one, and whether it is best to study the text in relation to written or spoken speech.